2021
DOI: 10.3390/vetsci8070127
|View full text |Cite
|
Sign up to set email alerts
|

Honey Bee Health

Abstract: Honey bee health is a very important issue that has recently caught the increased interest of researchers, stakeholders and citizens [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…However, this downregulation of the energetically expensive immune system results in increased susceptibility to pathogens. This phenomenon is evidently related to reports about honey bee collapse, where the most significant colony losses occur during overwintering [1]. Importantly, both generations of honey bees share the same genetic background, and differences in health and immunity develop only due to the influence of the annual seasonal cycle.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, this downregulation of the energetically expensive immune system results in increased susceptibility to pathogens. This phenomenon is evidently related to reports about honey bee collapse, where the most significant colony losses occur during overwintering [1]. Importantly, both generations of honey bees share the same genetic background, and differences in health and immunity develop only due to the influence of the annual seasonal cycle.…”
Section: Introductionsupporting
confidence: 70%
“…Honey bees play a significant role in ecology and produce biologically active substances that humans have long used to promote health. Various aspects of health, including at the molecular, microbial, and population levels, have recently gained increased interest from researchers, stakeholders, and citizens [1]. However, unlike humans, the standard parameters of honey bee health remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Almasri et al [48] explained that even mild exposure to pesticides can directly alter the physiological homeostasis of bees and particularly if the individuals exhibit a lack the core microbiota. Meanwhile, such behavioral alteration and physiological disruption caused due to pesticide exposure directly lead to lethal efects on bees at varying time intervals for diferent ages of bees [13,14,48].…”
Section: Behavioral and Physiological Efect Of Pesticidesmentioning
confidence: 99%
“…Although the putative causes of colony loss are still unclear, the combined efects of climate change, intensive agriculture, pesticides use, pest and pathogens, and biodiversity loss are some risk factors for global honeybee loss [12]. Earlier reports suggested that the extensive exposure of bees to pesticide incidents would possibly be a major factor for honeybee loss and colony decline [13][14][15][16][17]. In Ethiopia, widespread reports indicate that exposure to commonly used agricultural pesticides has been linked to the dramatic honeybee deaths and colony decline than any other factors in the country [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In light of the extraordinary response garnered by the previous Special Issue Honey Bee Health [1], the objective of the current Special Issue, Challenges and Advances in Bee Health and Diseases, is to delve further into the domain of bee health. This includes managed honey bees as well as wild bees, with a focus on several facets of bee pathogens and bee diseases in a series of research articles.…”
mentioning
confidence: 99%